The Effect of Quality of Information System Service on User Satisfaction Through Service Efficiency in A Web-Based Digital Diploma System - Rosa Selly Yudiasari; Metta Padmalia (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study was conducted in response to the need to improve the quality of digital academic services in higher education, particularly the issuance and verification of web-based digital diplomas. Accordingly, the study examines how information system service quality affects user satisfaction through service efficiency in the context of a web-based digital diploma system. The study employed a quantitative explanatory model using a cross-sectional approach. The research population consisted of Universitas Ciputra students and alumni, and purposive sampling was used to obtain 95 respondents who had experience using the digital diploma system. The data were analyzed through path analysis using IBM SPSS Statistics, supported by validity testing, reliability testing, classical assumption testing, the Sobel test, and bootstrap confidence intervals. The results show that information system service quality has a positive and significant effect on user satisfaction and service efficiency. Service efficiency also has a positive and significant effect on user satisfaction and significantly mediates the relationship between information system service quality and user satisfaction. The mediation is partial because the direct effect remains significant while the indirect effect through service efficiency is also significant. These findings indicate that a high-quality information system can increase user satisfaction both directly and through more efficient service delivery. Higher education institutions should therefore strengthen the technical quality of digital academic systems and ensure that these systems create effective services in actual practice. Improvements should focus on system usability, reliability, security, accuracy, process simplification, error reduction, and responsive helpdesk support. A web-based digital diploma system should consequently be viewed not merely as a tool for document digitization, but also as a strategic instrument for institutional digital transformation and the improvement of academic service quality.